[Bożonarodzeniowa karta okolicznościowa z Trzema Królami] . Christmas greeting card with the Three Magi - Toruń. (Toruń)
Red, black and blue print on white paper, with undivided back. Christmas greeting card contains a graphic image of the three Magi following a star with letter "s", with caption "Let us persist in our longing".